Skate or die: Unusual circumstances surrounding a natural cause of death. (February 2020) - Thicot, Frederique; Fracasso, Tony
Abstract: In a forensic pathologist's mind, a suspicious death scene involving inflicted injuries and a weapon always raises three possible hypotheses regarding the manner of death—homicide, suicide, or accident; the latter is slightly less common. We present a case of a 43-year-old homeless man with a history of chronic alcohol abuse who was found dead in a skate park in Geneva. He was inflicted with a stab wound to his abdomen, with a knife found in situ. With the suspicion of homicide, a crime scene investigation team, including a forensic pathologist, was summoned to the scene. However, further examination of the body revealed a deep cut with hesitation marks on the left forearm. This discovery raised the hypothesis of a suicide. Here, we have described the investigations made by the police and forensic department, along with the circumstances and autopsy findings that determined the cause of death as an effect of a natural disease. Highlights: Post mortem examination excluded the lethality of the stab and cut injuries. The Autopsy and histopathology confirmed the presence of an acute peritonitis due to a perforated peptic ulcer. Careful correlation of each post mortem finding is an essential aspect of the forensic pathologist's practice.